An intricate balance of hydrogen bonding, ion atmosphere and dynamics facilitates a seamless uracil to cytosine substitution in the U-turn of the neomycin-sensing riboswitch - Krepl, Miroslav; Vögele, Jennifer; Kruse, Holger; Duchardt-Ferner, Elke; Wöhnert, Jens; Sponer, Jiri (Nucleic acids research, 2018)
The neomycin sensing riboswitch is the smallest biologically functional RNA riboswitch, forming a hairpin capped with a U-turn loop-a well-known RNA motif containing a conserved uracil. It was shown previously that a U→C substitution of the eponymous conserved uracil does not alter the riboswitch structure due to C protonation at N3. Furthermore, cytosine is evolutionary permitted to replace uracil in other U-turns. Here, we use molecular dynamics simulations to study the molecular basis of this substitution in the neomycin sensing riboswitch and show that a structure-stabilizing monovalent cation-binding site in the wild-type RNA is the main reason for its negligible structural effect. We then use NMR spectroscopy to confirm the existence of this cation-binding site and to demonstrate its effects on RNA stability. Lastly, using quantum chemical calculations, we show that the cation-binding site is altering the electronic environment of the wild-type U-turn so that it is more similar to the cytosine mutant. The study reveals an amazingly complex and delicate interplay between various energy contributions shaping up the 3D structure and evolution of nucleic acids.
Keywords: mutace; Magnesium; Molecular Dynamics Simulation; draslík; hořčík; Base Pairing; vodíková vazba; cytosin; kationty; vazebná místa; Potassium; Cations; Cytosine; párování bází; simulace molekulární dynamiky; Nucleic Acid Conformation; Mutation; uracil; Ligands; konformace nukleové kyseliny; riboswitch; Nuclear Magnetic Resonance, Biomolecular; Neomycin; nukleární magnetická rezonance biomolekulární; Riboswitch; Uracil; Hydrogen Bonding; ionty; Ions; neomycin; ligandy; Binding Sites